2019
DOI: 10.1093/rof/rfz015
|View full text |Cite
|
Sign up to set email alerts
|

One Central Bank to Rule Them All*

Abstract: While global stock markets enjoy high returns on days surrounding Federal Open Market Committee (FOMC) meetings, there is no comparable result for other central banks either internationally or, more surprisingly, domestically. Neither announcement surprises nor currency moves drive these findings, which hold even for stocks with a domestic focus. The difference in announcement premia is not explained by economy size, exposure to multinationals, or policy activism. We conclude that the Fed exerts a unique impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…The results for June are only affected by the Fed's announcements because Korea did not conduct any meeting for interest rate decisions in June. In addition, as mentioned above, Brusa, Savor, and Wilson [ 12 ] showed that FOMC announcements have a unique impact on global equity prices, while those of non-US central banks do not affect global markets or their domestic stock markets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results for June are only affected by the Fed's announcements because Korea did not conduct any meeting for interest rate decisions in June. In addition, as mentioned above, Brusa, Savor, and Wilson [ 12 ] showed that FOMC announcements have a unique impact on global equity prices, while those of non-US central banks do not affect global markets or their domestic stock markets.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Brusa, Savor, and Wilson [ 12 ] examined stock markets in 38 countries from 1973 to 2016, finding that, whereas their stock markets are strongly affected by the Fed's policy announcements, there is no comparable result for other central banks either internationally or domestically. Their results are consistent with previous studies showing that US monetary policy exerts substantial influence in the global financial system via changes in international asset prices, capital flows, and credit growth (e.g.…”
Section: Related Literaturementioning
confidence: 99%
“…Our empirical assessments are based on data measured at monthly frequency. 6 The sample period is restricted by the availability of the US monetary policy surprise Furthermore, inclusion in MSCI market indices requires the stock to fulfil certain quality criteria and the opportunity for both domestic and foreign investors to 7 For more details see appendix A.…”
Section: Datamentioning
confidence: 99%
“…In contrast, Fratzscher, Duca, and Straub (2016) conclude 7. Some papers also look at the spillovers to exchange rates or foreign equities, such as Kim and Nguyen (2009), Wongswan (2006), Wongswan (2009), Ammer, Vega, andWongswan (2010), andBrusa, Savor, andWilson (2020).…”
Section: Related Literaturementioning
confidence: 99%